PROFIL PEMECAHAN MASALAH ARITMATIKA SOSIAL SISWA KELAS VII A SMPN 2 JEMBER BERDASARKAN TAHAPAN POLYA DITINJAU DARI GAYA BELAJAR V-A-K (VISUAL, AUDITORIAL, KINESTETIK) - Yuliyanti, Resdiana Putri; Hobri, Hobri; Suharto, Suharto (Department of Mathematics Education , University of Jember, 2017)
Abstract. The purpose of this research is to describe the problem solving profile of social arithmetic by students at VII A in SMPN 2 Jember through the Polya phasis in terms of V-A-K learning style (Visual, Auditorial, and Kinesthetic). The type of this research is descriptive research with qualitative approach. Methods of data collection in this research are learning style questionnaire, problem solving’s test, interviews. Subjects in this research are students who tend to visual, auditorial, and kinesthetic learning style. The data analyzed in this research is learning style questionnaire, test answer sheet, and interview result. Data analysis is based on the problem solving indicator based on Polya phasis. The result of this research are: at the understanding the problem for all types of question phase, all students are equally still unable to carry out the phase. At the making plans phase, visual studets are only able to carry out this phase at visual type problem and tend to be able to both other types, whereas auditorial and kinesthetic students have not been able to kinesthetic type problem and tend to be able to both other type. At the executing the plan phase, visual students are only able to carry out this phase on visual type problems and tend to be able to both other types, whereas auditorial and kinesthetic students tend to be capable of auditorial type problems and have not been able to both types. At the re-examining phase, visual students have not been able to perform this phase on kinesthetic types and tend to be able to both other types, whereas auditorial students are only capable of auditorial type problems, tend to be in the visual type, and not yet capable of kinesthetic types, Kinesthetic students tend to be capable of all three types of questions. Keywords: Problem solving, social arithmetic problems, polya phases, visual, auditorial, and kinesthetic’s learning style